Knowledge and language ability are the fundamental sources of Muslim intellectual virtue - Yaacob, Solehah@Nik Najah Fadilah (New Turkey Strategic Research Center, 2017)
The study focuses on revisiting the combination of knowledge and language as an intellectual virtue of sources foundation on Muslim scholars. The mental process connection in the language learning process is a critical thinking in human mind capability as a major faculty in human life. The tool used as a measurement of this knowledge ability consists of several processes including experience and education background. To emphasize the ability of knowledge background, the researcher highlights some major aspects of philosophical approach and language benchmark as a fundamental discussion of the paper. To embark the paper argumentation, the researcher compares between traditional sciences and Modern Scientific theory . An analytical and critical study of the both concepts become the methodology of the discussion